Aplikasi Keliling Nusantara Edisi Sumatera Berbasis Android dan iOS - Angga Apridianto; Kodrat Iman Satoto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Diversity of art and culture in Indonesia should be preserved so as not to become extinct in the face of times so that it can be passed on to generations to come. Many of the people of Indonesia who forget about the culture to identity of the area because of several factors such as the people of indonesia more interested of the western culture than self culture, the region of Indonesia which large also cause people’s reluctance to learn because of constrained of time, distance and cost as well as limitations of the media information about the art and culture that currently can only be learned through pictures and visit the location of art and culture directly make the introduction of art and culture to people of indonesia not yet optimal. Therefore required a media so that people can learn more about the wealth of art and culture without having to visit directly into the location of the arts and cultures its. “Keliling Nusantara Edisi Sumatra” application that was built can be the way to preserve the national culture. The function of this application as a learning media for recognize the diversity of arts and cultures of Indonesia on the island of Sumatra. This application is built using Mobione Studio and running on Android and iOS devices. The application is made using the UCD (User Centered Design) which has been mapped to multimedia development methods by Luther from the stage specify the context of use and specify the users and organisational requirements are mapped into the concept, the stage produce design solutions are mapped into the design, production and collecting material as wellas the evaluate design againts the user requirements are mapped into the stage of testing and distribution. The results produced an application based on Android and iOS contains folks song and lyrics and sound, traditional dress, traditional homes, custom traditions, traditional weapons, traditional dance, tradition musical instrument, the symbol of the region, the anniversaries, the name of the capital city, location, area and amount of population and the flora and fauna typical area on the island of Sumatra. The application goes well on the Android operating system version 2.2-4.X and iOS version 5-7 correspond with the functionality, specification and design of desired.